WHO histologic classification is a prognostic indicator in thymoma - Kondo, Kazuya; Yoshizawa, Kiyoshi; Tsuyuguchi, Masaru; Kimura, Suguru; Sumitomo, Masayuki; Morita, Junji; Miyoshi, Takanori; Sakiyama, Shoji; Mukai, Kiyoshi; Monden, Yasumasa (The Annals of thoracic surgery, 2004)
The histologic classification of thymoma has remained a subject of controversy for many years. In 1999, the World Health Organization Consensus Committee published a histologic typing system for tumors of the thymus. We reclassified a series of 100 thymomas resected at Tokushima University Hospital and four affiliated hospitals in Japan between 1973 and 2001 according to the World Health Organization histologic classification and reported its clinicopathologic relationship and prognostic relevance. There were 8 type A, 17 type AB, 27 type B1, 8 type B2, 12 type B3, and 28 type C thymomas. The frequency of invasion to neighboring organs increased according to tumor subtype in the order A (0%), AB (6%), B1 (19%), B2 (25%), B3 (42%), and C (89%). There was no recurrence in patients with type A, AB, or B2 thymoma. The recurrence rates of patients with B1, B3, or C thymoma were 15%, 36%, and 47%, respectively. The disease-free survival rates were 100% for types A and AB, 83% for types B1 and B2, 36% for type B3, and 28% for type C thymoma at 10 years. There were significant differences in disease-free survival between types A and AB and types B1 and B2 ( p = 0.0436), and between type B3 and type C ( p = 0.042). By multivariate analysis, only Masaoka clinical stage ( p = 0.002) showed significant independent effects on disease-free survival. The 10-year survival rates of types A and AB, types B1 and B2, type B3, and type C thymoma were 100%, 94%, 92%, and 58%, respectively. The current study confirmed the World Health Organization histologic classification as a good prognostic factor.